Prevalence and incidence of primary autoimmune hemolytic anemia and cold agglutinin disease in the United States, 2016–2023 - Sylvie Bozzi; Siddhi Umarje; Kalyani Hawaldar; Jennifer Tyma; Brad Ward; Jill Schinkel; Barnabie Agatep; Zulkarnain Pulungan; Natalia Petruski-Ivleva (PLoS ONE, 2025)
Background and aims Autoimmune hemolytic anemia (AIHA) and cold agglutinin disease (CAD) are debilitating conditions characterized by chronic hemolysis and severe anemia. The existing epidemiological estimates in the United States (US) remain limited because of the rarity of AIHA and CAD. This retrospective study aims to update the epidemiology of AIHA and CAD in the US from 2016 to 2023 by separately analyzing administrative claims data from Optum’s de-identified Clinformatics® Data Mart (Optum CDM), Inovalon’s Medical Outcomes Research for Effectiveness and Economics (MORE2) Registry, and Medicare Fee for Service (FFS). Methods The study consisted of patients aged ≥18 years with 180 days of continuous enrollment in their health plan. The index date was the first observed claim with AIHA or CAD ICD-9/10 diagnosis codes. The 2016–2021 US Census data were used to standardize incidence and prevalence estimates by age and sex. The results were presented by the US states. Results The AIHA incidence ranged from 1.4 to 6.6 per 100,000 persons across the databases. The CAD incidence ranged from 0.6 to 1.2 per 100,000 persons across the databases, with Medicare FFS estimates being the highest. Prevalence estimates also varied, with the AIHA 1-year prevalence ranging from 4.2 to 20.6 per 100,000 persons and CAD from 1.4 to 3.1 per 100,000 persons across the databases. Conclusion This multi-database analysis provides the updated epidemiological estimates of AIHA and CAD in the US, showing a higher incidence and prevalence in females than males, with both conditions increasing with age. However, no clear geographic pattern emerged across the US.